Differentiation of sarcoidosis from tuberculosis using real-time PCR assay for the detection and quantification of Mycobacterium tuberculosis - Zhou, Y.; Li, H.P.; Li, et al., Q.H. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Background: The clinical and pathological features of sarcoidosis and tuberculosis may mimic each other, and when the caseous necrosis is not seen in tuberculosis tissue, differentiation is not easy. Objective: This study evaluates the ability of real-time PCR quantification and sets the quantitive value to differentiate sarcoidosis from TB. Methods: Formalin-fixed and paraffin-embedded sections of biopsy samples, from 104 patients with sarcoidosis, 31 patients with tuberculosis, and 55 controls with other respiratory diseases (26 with nonspecific lymphadenitis and 29 with emphysema bullae), were collected to amplify insertion sequence IS986 of Mycobacterium tuberculosis (MTB) genome by real-time quantitative PCR. The diagnostic performance of qualitative and quantitative analysis of real-time quantitative PCR was assessed by receiver-operating characteristic (ROC) curves. Results: MTB DNA was detected in 20 of the 104 sarcoidosis samples and 7 of the 55 control samples, but was detected in all of the 31 tuberculosis samples. The numbers of MTB genomes were 0~4.71x103copies per ml in sarcoidosis samples, 1.58x102~5.43x107copies per ml in tuberculosis samples and 0~1.02x103 copies per ml in controls with quantitative analysis. Receiver-operating characteristic (ROC) curves showed that MTB genome quantification had greater diagnostic performance than MTB genome qualitation in discriminating patients with sarcoidosis from those with tuberculosis (area under the ROC curves: 0.994 vs 0.904, P